Mind the gap: Khilafah fil-Arḍ as an Islamic sustainable human development paradigm - Ismail, Norbani (Al-Itqan Journal, 2021)
This paper explores the interdisciplinary approach of bridging the secular understanding of United Nation‘s Sustainable Human Development (UN SDGs) with the Islamic perspective of Tawhīd. This paper showcases the duality between the physical and the metaphysical understanding of sustainable human development for Muslim societies: employing the concept of Khilāfah as an act to progress societal development, while answering Islamic duties as a vicegerent of God. In many instances, Muslim women are internalizing the concept of Khilāfah as an emancipatory tool of reclamation against the normative understanding of agency as understood in liberal feminist politics. Filling the gap of the secularistic UN‘s SDGs require a rereading of world history, and urges the deconstruction of what sustainable human development ought to be for Muslim societies.